RITUAL ASYEIK : MAKNA SIMBOLIK DAN PENGETAHUAN TRADISIONAL MASYARAKAT KERINCI - Muhammad Tory Prasetya; Maskota Delfi; Fajri Rahman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the symbolic meanings and traditional knowledge system embedded in the Asyeik Ritual among the Kerinci people of Indonesia. The Asyeik Ritual is a cultural heritage tradition that originated in the pre-Islamic period and has undergone a process of acculturation with Islamic teachings. To this day, the ritual continues to be practiced in various contexts, including healing ceremonies, the fulfillment of vows, the removal of misfortune, and the purification of ancestral heirlooms. This research employed an ethnographic approach conducted between 2024 and 2026 through participant observation and in-depth interviews with gurui, salih, customary leaders, and community members in the Kerinci region. The findings reveal that the Asyeik Ritual functions not only as a traditional healing practice but also as a repository of local knowledge governing the relationship between humans, nature, ancestors, and the spiritual realm. The symbols, chants, ritual objects, and ceremonial actions involved in the ritual reflect the cosmological worldview of the Kerinci people and serve as a medium for the intergenerational transmission of cultural knowledge. In addition to strengthening social solidarity and cultural identity, the ritual contributes to the preservation of local values amid ongoing social change. As an element of Indonesia’s Intangible Cultural Heritage, the continuity of the Asyeik Ritual faces challenges from modernization, the declining number of ritual practitioners, and the limited availability of supporting resources. Therefore, community-based preservation and revitalization efforts are essential to ensure its sustainability.